A comparison of conventional compression plates and locking compression plates using cantilever bending in an ilial fracture model - Bruce, C W; Gibson, T W G; Runciman, R J (Veterinary and comparative orthopaedics and traumatology, 2014)
The purpose of this study was to compare the stiffness, yield load, ultimate load at failure, displacement at failure, and mode of failure in cantilever bending of locking compression plates (LCP) and dynamic compression plates (DCP) in an acute failure ilial fracture model. Our hypothesis was that the LCP would be superior to the DCP for all of these biomechanical properties. Ten pelves were harvested from healthy dogs euthanatized for reasons unrelated to this study and divided into two groups. A transverse osteotomy was performed and stabilized with either a 6-hole DCP applied in compression or a 6-hole LCP. Pelves were tested in cantilever bending at 20 mm/min to failure and construct stiffness, yield load, ultimate load at failure, displacement at failure, and mode of failure were compared. The mean stiffness of DCP constructs (193 N/mm [95% CI 121 - 264]) and of LCP constructs (224 N/mm [95% CI 152 - 295]) was not significantly different. Mean yield load of DCP constructs (900 N [95% CI 649 -1151]) and of LCP constructs (984 N [95% CI 733 -1235]) was not significantly different. No significant differences were found between the DCP and LCP constructs with respect to mode of failure, displacement at failure, or ultimate load at failure. Our study did not demonstrate any differences between DCP and LCP construct performance in acute failure testing in vitro.